2007
DOI: 10.1128/jvi.02876-06
|View full text |Cite
|
Sign up to set email alerts
|

Lassa Virus Infection in Experimentally Infected Marmosets: Liver Pathology and Immunophenotypic Alterations in Target Tissues

Abstract: Lassa virus causes thousands of deaths annually in western

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
128
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 41 publications
9
128
0
Order By: Relevance
“…In contrast, in good correlation with our results, in progressed LF patients, fatal infection was correlated with low or undetectable levels of proinflammatory cytokines/chemokines, including IL-8 and IP-10 (39). At present, the immunosuppressive phenotype of progressed LASV infection in humans or in nonhuman primates is a well-accepted concept (7,15,46,49,62). Our previously reported gene expression analysis of human peripheral blood mononuclear cells (PBMC) from healthy donors exposed to LASV has shown that IFN-related genes and genes involved in apoptosis, NF-B, and coagulation pathways were among the genes most affected by LASV (61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in good correlation with our results, in progressed LF patients, fatal infection was correlated with low or undetectable levels of proinflammatory cytokines/chemokines, including IL-8 and IP-10 (39). At present, the immunosuppressive phenotype of progressed LASV infection in humans or in nonhuman primates is a well-accepted concept (7,15,46,49,62). Our previously reported gene expression analysis of human peripheral blood mononuclear cells (PBMC) from healthy donors exposed to LASV has shown that IFN-related genes and genes involved in apoptosis, NF-B, and coagulation pathways were among the genes most affected by LASV (61).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to filovirus VHF (23), in LF patients, the profound shock, vascular damage, and hemorrhage in late-stage victims of Old World arenaviruses are not associated with a "cytokine storm." In fact, we (15,35,38) and others (5-7, 27, 39, 40) showed that LASV replication in vitro and in vivo is associated with the suppression of proinflammatory responses, impaired activation of innate immune cells, and delayed cytotoxic T cell responses, contributing to unchecked viremia and fatal outcomes.…”
mentioning
confidence: 99%
“…18 As with the macaque model, experimental infection of common marmosets with LASV (Josiah strain) results in a systemic viral disease with high viremia and high viral RNA load in tissues and elevated liver enzymes. 18,19 Morphologic features mimic those described in human cases of fatal LF, and include hepatic and adrenal necrosis, lymphoid depletion and interstitial nephritis.…”
Section: -10mentioning
confidence: 76%
“…2,61 Experimental ZEBOV infection of macaques by intramuscular injection of 1,000 PFU of virus results in a rapid, fatal disease. 14,18,19 Beginning at day 4 post-infection, macaques experienced anorexia coinciding with the onset of fever. Shortly after these initial findings, petechial rash ( Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation